SINTESIS DAN KARAKTERISASI POLIURETAN BERPORI DARI GLISEROL DAN ETILENADIAMINA SERTA UJI KAPASITAS ADSORPSINYA TERHADAP SENYAWA KARSINOGENIK PADA ASAP ROKOK - , RICKY ANDI SYAHPUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Synthesis and characterization of porous polyurethane from glycerol and ethylenediamine with its adsorption capacity toward carcinogenic compounds on cigarette smoke was conducted. Porous polyurethane was synthesized by variations volume of glycerol toward polyethylene glycol (PEG) 1000 and 4,4'- diphenylmethane diisocyanate (MDI). The volume ratio of glycerol toward (PEG 1000 and MDI) was 0/3, 1/3, 2/3, 3/3, and 4/3. Polyurethane with an optimum ratio of glycerol was added ethylenediamine with some variations. Dried at 50 Â°C for 3 hours. Polyurethane was characterized by FT-IR, HBI testing, swelling degree calculating, determining of specific surface area, average pore radii, and total pore volume with GSA, and tested resistance to solvents and adsorption capacity of the adsorbent with smoke flowing. Furthermore, the adsorbent with carcinogenic compound was analyzed by FT-IR and it was extracted with dichloromethane. The extract was analyzed by GC-MS. The results of FT-IR analysis showed that the porous polyurethane with the addition of glycerol and ethylenediamine can be performed. Based on the HBI and swelling degrees calculation, the optimum condition of polyurethane which was the ratio 1/3 (PU1). The addition of ethylenediamine which produced the character foam was added 0.05 mL (PU1E1). Under the GSA, PU1 and PU1E1 have isotherm adsorption type I (microporous) with specific surface area, average pore radii, and total pore volume sequentially, PU1 was 17.128 m2/g